Perbandingan Struktur Klausa Bahasa Arab dan Bahasa Indonesia: Penelitian Analisis Kontrastif dalam Koran As-Syarq Al-Awsath dan Koran Republika - Dedi Supriyanto (Program Studi Magister Linguistik Terapan UNJ, 2016)
The objectives of this research are to explain the Indonesian clause structure, the Arabic clause structure, and the similarities and the differences between clause structure in Arabic and in Indonesian. This research also include the prediction of the learning difficulties of Arabic for Indonesian learners. The data was collected through Arabic Newspaper â€œAlAsyraq AlAwsath Onlineâ€ and Indonesian Newspaper â€œRepublika Onlineâ€. This research used a qualitative approach using Content Analysis methods. Through the research there are found more differences than similarities between Arabic clause structure and Indonesian. The result of the reserach are: 1). Indonesian and Arabic have the same clause structure in Subject-Predicate (S-P) and Predicate-Subject (P-S), 2). The differences are in gender, tenses, number, and iâ€™rab. Based on the research, it is predicted that Indonesian students will find difficulties in learning Arabic.